INFLUENCE OF SOMATIC MUTATIONS OF KRAS, NRAS, BRAF AND MICROSATELLITE INSTABILITY STATUS ON SURVIVAL OF COLORECTAL CANCER PATIENTS WITH PERITONAL CARCINO - V. P. Shubin; Yu. A. Shelygin; S. I. Achkasov; O. I. Sushkov; A. A. Ponomarenko; A. I. Arzamastseva; A. S. Tsukanov (Сибирский онкологический журнал, 2020)
Purpose: to evaluate the effect of somatic mutations of the KRAS, NRAS, BRAF genes and the status of microsatellite instability on the overall and disease-free survival of patients undergoing cytoreductive surgery with hyperthermic intraperitoneal chemotherapy.Material and Methods. From 2012 to 2018, the study included 45 patients who underwent surgery for synchronous peritoneal carcinomatosis with colorectal cancer. In all patients, mutations of the KRAS, NRAS, BRAF genes and MSI status of the tumor and peritoneum metastases were determined using Sanger sequencing, fragment analysis and digital droplet polymerase chain reaction. The effect of mutations on patient survival was evaluated.Results. The prevalence of somatic mutations was 69 % of patients. The discordance between the tumor and peritoneum metastases was 9 %. All tumors and peritoneum metastases were microsatellite stable. KRAS, NRAS, BRAF mutations did not affect the overall and disease-free survival (p=0.87 and p=0.85, respectively).Conclusion. Somatic mutations in the KRAS, NRAS, or BRAF genes are not a prognostic factor affecting the overall and relapse-free survival of colorectal cancer patients with peritoneal carcinomatosis. The molecular status of primary tumor may differ from the status of peritoneal metastasis. It should be taken into account when prescribing targeted drugs.